Aggregation-induced emission-active tetraphenylethylene derivatives containing arylimidazole unit for reversible mechanofluorochromism and selective detection of picric acid. (October 2020) - Zhang, Shuaishuai; Huang, Yiping; Kong, Lin; Zhang, Xuanjun; Yang, Jiaxiang
Abstract: Subtle modification of molecular structure can play a crucial role in determining photophysical properties and stimuli-responsive behavior. Herein, four aggregation-induced emission (AIE)-active tetraphenylethylene-based positional isomers S1, S2, S3 and S4 have been designed and synthesized. S2 and S4 exhibit higher fluorescence quantum yield (ΦFL ) as compared to S1 and S3, respectively, which was due to the positional isomerism. In addition, all four isomers exhibit reversible mechanofluorochromic (MFC) behavior with mechanical-induced emission enhancement (MIEE), which was studied using powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). S1 and S2 display better MFC activities, compared with S3 and S4, due to opened phenylimidazole presenting a more twisted conformation. Moreover, they can detect picric acid (PA) in a highly selective and sensitive manner in aqueous media, due to the excellent proton-binding property of the imidazole group, which was verified by 1 H NMR spectra and supported by theoretical calculations. Overall, tetraphenylethylene containing arylimidazole derivatives described herein will efficiently expand the development of design principles to supply diverse multifunctional tools for material science and material engineering. Graphical abstract: Image 1 Highlights: A series of isomers were synthesized by combination of TPE and arylimidazole units. Isomers exhibit MFC behavior with mechanical-induced emission enhancement. Isomers can detect PA in a highly sensitive manner in aqueous medium.